Effects of home-based dual-hemispheric transcranial direct current stimulation combined with exercise on upper and lower limb motor performance in patients with chronic stroke. Issue 15 (17th July 2022) - Prathum, Thatchaya; Piriyaprasarth, Pagamas; Aneksan, Benchaporn; Hiengkaew, Vimonwan; Pankhaew, Thitinat; Vachalathiti, Roongtiwa; Klomjai, Wanalee
Abstract: Purpose: This study aimed to determine the effects of home-based dual-hemispheric transcranial direct current stimulation (dual-tDCS) combined with exercise on motor performance in patients with chronic stroke. Materials and methods: We allocated 24 participants to the active or sham group. They completed 1-h home-based exercise after 20-min dual-tDCS at 2-mA, thrice a week for 4 weeks. The patients were assessed using the Fugl–Meyer Assessment (FMA), Wolf Motor Function Test, Timed Up and Go test, Five Times Sit-to-Stand Test, Six-meter Walk Test, and muscle strength assessment. Results: Compared with the sham group, the active group showed improved FMA scores, which were sustained for at least 1 month. There was no between-group difference in the outcomes of the functional tasks. Conclusion: Home-based dual-tDCS could facilitate motor recovery in patients with chronic stroke with its effect lasting for at least 1 month. However, its effects on functional tasks remain unclear. tDCS is safe and easy for home-based self-administration for patients who can use their paretic arms. This could benefit patients without access to health care centres or in situations requiring physical distancing. This home-based tDCS combined with exercise has the potential to be incorporated into telemedicine in stroke rehabilitation. IMPLICATIONS FOR REHABILITATION: Twelve sessions of home-based dual-tDCS combined with exercises (3 days/week for 4 weeks) facilitated upper and lower limb motor recovery in patients with chronic stroke compared with exercise alone, with a post-effect for at least 1 month. Home-based tDCS could be safe and easily self-administrable by patients who can use their paretic arms. This intervention could be beneficial for patients living in the community without easy access to a health care centre or in situations where physical distancing is required.